(untitled) (GYMNASIUM, 2017)
This research aims to investigate the evolution of the fitness level in pubertal pupils from urban areas. The measurements addressed the middle school pupils from General School 30, Braşov, and were carried out by applying the Eurofit battery of tests to both genders. A comparative analysis of the avereges has revealed a general deterioration of fitness in final year middle school, illustrated by either a decrease in level, or by negligible increases. The applied tests showed that the general body values, indicate irrelevant evolutions. Similarly, irellevant increases or either decreases were recorded for measuring the palm flexor strength, performing the 10x5m shuttle run, as well as determining the cardiorespiratory endurance test by applying the 24x20m shuttle run. Following physical abilities scored increased values: standing long jump in final grade middle school pupils, girls and boys, upper body reaction time in boys. Improving upgrading fitness requires the development and application of appropriate physical training programmes, within the context of the formal and the informal activities.